Extremities analysis over Parambikulam Aliyar project basin of Tamil Nadu - Velusamy, Guhan; Vellangiri, Geethalakshmi; Ayyavoo, Raviraj; Tamilarasan, Sankar (MAUSAM, 2025)
Study examined the evaluation of contemporary space-time patterns of extreme temperature and precipitation values in Parambikulam Aliyar Project basin for the years 1981 to 2017. The investigation of extremes conducted in Aliyar sub-basin Catchment area, Aliyar sub-basin command area, Palar sub-basin Catchment area, Palar sub-basin command area, PAP hill region, PAP plain region, PAP whole basin. The results clearly revealed that represent consecutive dry days in Aliyar sub-basin Catchment area showed slightly increasing trend (from 56 days in 1981 to 63 days in 2017) which could served as an indicator of dryness and chance of seasonal drought occurrence. In the Palar sub-basin catchment areas under the PAP basin, consecutive dry days do not show any trend. With regards to consecutive wet days, PAP hill areas are showing a significant positive trend (P-Value of 0.038, and R2 of 0. 432). The trend in the simple precipitation intensity index (SDII) showed slight upward movement (7 to 8mm/ day). In the command area, only rx5day showed a major increase of 1.25 mm/year variation. The mean reduction in the mean daily temperature and mean minimum temperature as per the Sen’s slope estimator stands at -0.011 °C/ Year and -0.003 °C/ year for Aliyar sub-basin catchment and -0.012 °C/ Year and -0.003 °C/ year for Aliyar command area. Spatial extent of PAP hilly region and PAP as a whole showed a slightly rising trend in precipitation extreme events. However, in PAP plain areas, slight reductions were noticed in r20mm, rx3day, and rx5day precipitation indices. These findings highlight the importance of long term climate data analysis for decision making and adaptation strategies in the face of climate extremities.